2023
DOI: 10.3390/ijerph20156525
|View full text |Cite
|
Sign up to set email alerts
|

Differential Magnitude of Resilience between Emotional Intelligence and Life Satisfaction in Mountain Sports Athletes

Abstract: The field of mountain sports has its own characteristics, different from other sports modalities. Emotional intelligence and resilience not only refer to the adaptive capacity that can be developed after an adverse experience, but can also be factors that positively affect sporting performance in extreme conditions. In this study, 4818 athletes from the Spanish Federation of Mountain Sports and Climbing participated; 2696 were men (67.1%) and 1322 were women (32.9%), with a mean age of 49.42 years (±11.9). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(83 reference statements)
2
0
0
Order By: Relevance
“…More than perceiving and understanding emotions, the results of the present study indicate that participating in organized sports contributes to adolescents developing their ability to use and direct their emotions toward self-directed, constructive activities to facilitate higher achievements and performance, which in turn contributes to their self-esteem and well-being. This finding confirms and extends previous studies that have shown stronger associations between the use of emotion, self-esteem, and life satisfaction in adult athletes [ 42 , 55 ] when compared to the remaining emotional intelligence dimensions. Interestingly, results showed that the indirect effect of use of emotion on life satisfaction via self-esteem was larger than the direct effect (59.7% vs. 40.3%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More than perceiving and understanding emotions, the results of the present study indicate that participating in organized sports contributes to adolescents developing their ability to use and direct their emotions toward self-directed, constructive activities to facilitate higher achievements and performance, which in turn contributes to their self-esteem and well-being. This finding confirms and extends previous studies that have shown stronger associations between the use of emotion, self-esteem, and life satisfaction in adult athletes [ 42 , 55 ] when compared to the remaining emotional intelligence dimensions. Interestingly, results showed that the indirect effect of use of emotion on life satisfaction via self-esteem was larger than the direct effect (59.7% vs. 40.3%).…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the small association between youth sports participation and life satisfaction (see correlation coefficient in Table 1) was not supported when two mediators (emotional intelligence and self-esteem) were considered in the path model. This finding is consistent with recent research [24,54] and suggests that adolescents participating in organized sports are more satisfied with their lives when they are (more) able to perceive and use their emotions and, consequently, experience a more positive global evaluation of themselves [55]. Previous research has demonstrated that regular sports participation may foster opportunities for social interactions and relatedness in a formal/structured context under the supervision of coaches [43,56], helping adolescents to better perceive, understand, and use their emotions to facilitate performance, as well as experiencing more feelings of self-acceptance and self-worth [10,25].…”
Section: Effects Of Sports Participation On Emotional Intelligence Se...supporting
confidence: 93%